2018
DOI: 10.1016/j.jdermsci.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid insensitivity by staphylococcal enterotoxin B in keratinocytes of allergic dermatitis is associated with impaired nuclear translocation of the Glucocorticoid Receptor α

Abstract: Background: staphylococcal enterotoxin plays an important role in patients with glucocorticoid (GC)resistant atopic dermatitis (AD), but the exact mechanism is not fully understood. Objective: The aim of this study was to investigate the mechanisms underlying the ability of staphylococcal enterotoxin B (SEB) to induce steroid insensitivity through impaired nuclear translocation of GRα in keratinocytes. Methods: The steroid-resistant AD induced by SEB was assessed by analyzing dermatitis score, dermal thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Colonization of Staphylococcus aureus up-regulates the expression of antimicrobial peptides such as human β-defensin 2 and -3 and RNAse7; however, IL-31 inhibits their expression and may accelerate the Staphylococcal infection [73]. Staphylococcal superantigen may also induce glucocorticoid insensitivity by inhibiting the nuclear translocation of glucocorticoid receptor α [74].…”
Section: Role Of Il-31 and Il-13/il-4 In Atopic Pruritusmentioning
confidence: 99%
“…Colonization of Staphylococcus aureus up-regulates the expression of antimicrobial peptides such as human β-defensin 2 and -3 and RNAse7; however, IL-31 inhibits their expression and may accelerate the Staphylococcal infection [73]. Staphylococcal superantigen may also induce glucocorticoid insensitivity by inhibiting the nuclear translocation of glucocorticoid receptor α [74].…”
Section: Role Of Il-31 and Il-13/il-4 In Atopic Pruritusmentioning
confidence: 99%
“…72 A recent study in glucocorticoid-resistant patients with atopic dermatitis found that exotoxin A (SEA) from Staphylococcus aureus increased FKBP51 expression in human epidermal keratin-forming cells (HaCaT), disrupted GRα nuclear translocation and inhibited GR signal-transduction. 73 Impaired nuclear translocation in keratinocytes resulted in a lower ratio of GRα in nucleus to GRα in cytoplasm, which had also been observed in psoriasis 74 and atopic dermatitis. 75 It has been proved that high level of GRβ expression is associated with GC insensitivity.…”
Section: Impaired Nuclear Translocation Of the Gr Complexmentioning
confidence: 80%
“…High FKBP51 levels may contribute to retention of GRα in the cytoplasm, which lead to GC resistance in keratinocytes. 73 Some investigators reported that melatonin (MEL) can hinder the nuclear translocation of GR by inhibiting the dissociation of Hsp90 from GR. They found that in mouse thymocytes, MEL did not affect the ability of GR to bind steroids, but rather inhibited the steroid effect by inhibiting the separation of Hsp90 from GR, allowing inactivated GR to remain in the cytoplasm.…”
Section: Impaired Nuclear Translocation Of the Gr Complexmentioning
confidence: 99%
“…Though glucocorticoids (GC) are a common therapeutic strategy in AD management, utilizing the glucocorticoid receptor (GR) to dampen the inflammatory reaction, some patients become unresponsive to treatment. Huang et al (2018) showed that SEB can block GC action by impeding the nuclear translocation of GR in keratinocytes, favoring the persistence of inflammation [58]. Also, staphylococcal enterotoxins can modulate the induction of myeloid-derived suppressor cells (MDSCs).…”
Section: Role Of S Aureus Toxins In the Disruption Of The Skin Bamentioning
confidence: 99%